The biology of the Cape hakes Merluccius capensis Cast. and M. paradoxus Franca in the Cape of Good Hope area - Botha, Louis,1940- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1980.